2008
DOI: 10.2903/j.efsa.2008.754
|View full text |Cite
|
Sign up to set email alerts
|

Safety of aluminium from dietary intake ‐ Scientific Opinion of the Panel on Food Additives, Flavourings, Processing Aids and Food Contact Materials (AFC)

Abstract: Following a request from the Commission, the Panel on Food Additives, Flavourings, Processing Aids and Food Contact Materials (AFC) was asked to provide a scientific opinion on the safety of aluminium from all sources of dietary intake. In the event the estimated exposure for a particular sub-group(s) is found to exceed the Provisional Tolerable Weekly Intake, a detailed breakdown by exposure source should be provided. Aluminium occurs naturally in the environment and is also released due to anthropogenic acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
70
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(89 citation statements)
references
References 263 publications
(444 reference statements)
2
70
1
4
Order By: Relevance
“…Aluminium sulphates (E 520-523) and sodium aluminium phosphate (E 541) are authorised as food additives in the EU according to Annex II of Regulation ( The safety of aluminium from dietary intake was evaluated in 2008 by the EFSA Panel on Food Additives, Flavourings, Processing Aids and Food Contact Materials (EFSA, 2008). Based on the range of available NOAEL and LOAEL, and applying a weight of evidence approach, the Panel established a TWI of 1 mg aluminium/kg bw per week.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aluminium sulphates (E 520-523) and sodium aluminium phosphate (E 541) are authorised as food additives in the EU according to Annex II of Regulation ( The safety of aluminium from dietary intake was evaluated in 2008 by the EFSA Panel on Food Additives, Flavourings, Processing Aids and Food Contact Materials (EFSA, 2008). Based on the range of available NOAEL and LOAEL, and applying a weight of evidence approach, the Panel established a TWI of 1 mg aluminium/kg bw per week.…”
Section: Discussionmentioning
confidence: 99%
“…The EFSA AFC Panel (EFSA, 2008) reported effects on male reproductive organs and/or semen after oral administration in rabbits (LOAEL 6.4 mg Al/kg bw per day) and dogs (NOAEL 27 mg Al/kg bw per day). No effects on male and female fertility were observed in the rat after oral dietary administration.…”
Section: Discussionmentioning
confidence: 99%
“…Within the last decade, aluminum (Al)-containing nanomaterials (NMs) have been widely used not only for industrial applications, but also in consumer products, due to their higher reactivity compared to the bulk form [1,2,3,4]. Forms of Al, both in the micro-and the nano-size, are present in food and consumer products [1,5] due to their use as rming, anticaking, neutralizing, emulsifying and texturizing agents, as well as for cooking tools [6], waste water treatment [7,8] and in medical and hygiene products such as toothpaste [9,10,11]. Nevertheless, their potential toxicity has not been fully evaluated, leading to major concerns from consumers and public health agencies [12].…”
Section: Introductionmentioning
confidence: 99%
“…According to exposure estimates from the European Food Safety Authority (EFSA), consumers can absorb up to 2.3 mg Al /kg bw/week, more than twice the weekly tolerable intake (1 mg/kg bw/week) [7]. In addition, a recent study has estimated total consumer exposure to Al containing compounds, including contributions from products used in food (additives, contact materials) and in cosmetics, and concluded that adolescents were highly exposed [13].…”
Section: Introductionmentioning
confidence: 99%
“…Ezek a szabályzatok előírják, hogy az ivóvíz maximális alumínium tartalma 0,2 mg/l lehet, míg a napi bevitel egy felnőtt számára maximum 5 mg lehet (WHO, 1997) [9]. Az Európai Élelmiszerbiztonsági Hatóság (EFSA) legújabb (2008) szabályzata szerint a heti alumínium bevitel nem haladhatja meg az 1 mg/ttkg/hét, ami magába foglalja az ivóvízből, élelmiszerekből, környezetből emberi szervezetbe kerülő összalumínium-mennyiséget [10].…”
unclassified